Tailoring interface properties in wire-arc directed energy deposited dissimilar aluminum alloys through interlayer laser shock peening - Tianxing Chang; Huwei Zhang; Xuewei Fang; Minghua Ma; Senmu Zheng; Bingheng Lu; Ke Huang (Virtual and Physical Prototyping)
Dissimilar aluminium alloy components, leveraging the unique advantages of each alloy, provide exceptional strength, lightweight properties, corrosion resistance, and other desirable performance attributes. However, the internal porosity and undesirable element diffusion can weaken their interface performance, which often leads to premature fracture. Laser shock peening (LSP) is a process that produces a high-pressure plasma to exert plastic deformation on the near-surface of the material, which then tends to close porosity and improve mechanical properties. In this study, an interlayer LSP process was used to enhance the interface properties of 2319/5B06 dissimilar aluminium alloy components fabricated by wire-arc directed energy deposition. The results show that interlayer LSP effectively reduces the aggregation of coarse precipitates and porosity, and significantly improves the mechanical properties of the components. Notably, the elongation (6.9%) of the interlayer LSP-treated specimen with 5B06 at the bottom and 2319 at the top increased by 130% as compared to those of the as-built counterparts, while the ultimate tensile strength (245.8 MPa) also increased by 23.6%. The results of this study offer a process reference for microstructure optimisation and property enhancement at the interfaces of dissimilar alloy components fabricated by direct energy deposition.